ANALISIS PUTUSAN LEPAS PADA TINDAK PIDANA MEMASUKI RUMAH ORANG LAIN SECARA MELAWAN HUKUM (STUDI PUTUSAN PENGADILAN TINGGI DKI NOMOR 451/PID/2019/PT.DKI) - Nina Maulanny Herlan; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2020)
The criminal act of entering someone else’s house against the law is regulated in Book II Criminal Code, in Article 167 section (1) of the Criminal Code. For the case appointed by the author, the defendant was charged with Article 167 section (1) of the Criminal Code by the general prosecutors. This research background and reasons for writing by differences in the decisions handed down by the Panel of Judges at the South Jakarta District Court which convicted a defendant while the DKI District Superior Court declared a defendant free from all charges (ontslag van rechtsvervolging). This research is aimed to analyze and find out the judge’s consideration in giving a defendant free from all charges on the crime of entering someone else’s house against the law in Decision Number 451/PID/2019/PT.DKI. The research method used in this study is a normative research method based on literature study materials and interviews with practitioners and academics. The results of this study revealed that the consideration of the judge’s decision to release the defendant Zulkarnaen has been correct because the action of the accused was not a crime but a civil act in which there has been an disputes over land and building ownership between the defendant and H. Ashari Angkat Sutan’s biological child.